Marker-assisted Foreground Selection for Identification of Salt Tolerant Rice Genotypes (The Agriculturists, 2012)
ErratumIn the paper entitled Marker-assisted Foreground Selection for Identification of Salt Tolerant Rice Genotypes published in The Agriculturists 10(2): 1-8 (December 2012), the authors should be read as M. S. Alam, S. N. Begum, M. M. Islam, M. Moniruzzaman and M. A. K. Patwary instead of M. S. Alam, M. Salim, M. Moniruzzaman, J. A. Rashid and M. M. Islam (Authors changed on the online version on 13th June 2013).Marker Assisted Selection (MAS) technique was used to develop salt tolerant rice genotypes using molecular markers during June 2009 to November 2010 in the experimental field and Biotechnology Laboratory of Plant Breeding Division, Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh. FL-378 was identified as donor or male parent for saltol QTL and Binadhan-7 as recurrent or recipient parent which had high yield with short life cycle. Crossing was done between them and 10 F1 seeds were produced. PCR bands from all the 10F1 plants were scored as H represented heterozygous alleles for donor and recipient parent. Backcrossing was done to produce 105 BC1F1 seedlings. Foreground selection was performed with 72 BC1F1plants with a tightly linked salt tolerance marker RM21. Out of 72 plants, 33 plants were selected for RM21 showing H scores. The selected segregants were subjected to further recombinant and background selections at BC1F1 generation. These selected genotypess could be used for further foreground, recombinant and background selections with appropriate markers upto BC3 generation for the development of salt tolerant rice genotypes. DOI: http://dx.doi.org/10.3329/agric.v10i2.13128 The Agriculturists 2012; 10(2) 1-8